Analysing resistance element welding with upset auxiliary joining steel-elements under shear load - Meinhardt, Mario; Endres, Martin; Graf, Marcel; Lechner, Michael; Merklein, Marion (Procedia Manufacturing, 2019)
The multi-material-design, as one common lightweight design strategy, has to be intensified in order to reach climate-goals and to comply with exhaust gas emission limits. For joining sheet metal parts of different materials, enhanced joining technologies are used, which are specific for each application case. Within this paper, resistance element welding joints of sheet metals in shear load tests are investigated. The resistance element welding process with upset auxiliary joining steel-elements is a possibility for joining multi-material sheet metal parts, using the standard process of resistance spot welding. In order to assess the potential of this joining process, it is necessary to determine the load-bearing behaviour under shear load by shear tensile tests. The objective of this paper is to analyse the maximum shear strength for resistance element welding specimen with upset steel-elements in aluminium carrier sheets of different thicknesses. The geometry of the test specimen is adapted to resistance element welding process conditions. Failure behaviour under shear load is analysed and related to the applied upset elements. Finally, the maximum shear load strength of resistance element welding joints are presented and compared to similar joining technologies.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Joining Technology; Lightweight; Multi-Material; Resistance Element Welding; Shear Tensile Test